Conductive main grid silver paste for HIT solar cells and preparation method thereof

By using organic polymer resin and different types of silver powder in the conductive main gate silver paste of HIT solar cells, combined with low activation energy resin and catalytic curing agent, low temperature and short-term curing is achieved, solving the problems of long curing time, low adhesion and high resistance, and improving the production efficiency and electrical performance of the battery.

CN114496343BActive Publication Date: 2025-04-08NINGBO WEFLEX ELECTRONIC TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202111567659.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-21
Publication Date
2025-04-08
Estimated Expiration
2041-12-21

AI Technical Summary

Technical Problem

The existing conductive main gate silver paste for HIT solar cells has long curing time, low adhesion and high resistance.

Method used

Using a conductive main gate silver paste formula including organic polymer resin, sheet silver powder, nano silver powder and micro silver powder, a low-activation energy resin and a catalytic curing agent, a short-term curing is achieved at low temperature to form a pyramid structure to reduce resistivity and improve adhesion.

Benefits of technology

The curing time of conductive main gate silver paste is shortened, the resistivity is reduced, the adhesion is improved, the production cost is reduced, and the production and market competitiveness of HIT solar cells are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003422363740000141
    Figure BDA0003422363740000141
  • Figure BDA0003422363740000151
    Figure BDA0003422363740000151
  • Figure BDA0003422363740000152
    Figure BDA0003422363740000152
Patent Text Reader

Abstract

The present invention relates to the technical field of HIT solar cells. The present invention provides a conductive main grid silver paste for HIT solar cells, which comprises, by weight: 5 to 13 parts of an organic polymer resin, 30 to 60 parts of a first conductive powder, 30 to 60 parts of a second conductive powder, 0 to 5 parts of a curing agent, 1 to 10 parts of a solvent, and 0 to 5 parts of an auxiliary agent; the first conductive powder is a flaky silver powder, and the second conductive powder is composed of nano silver powder and micron silver powder, and the micron silver powder is a nearly spherical silver powder with high dispersibility. The present invention uses nano silver powder and micron silver powder as the second conductive powder, and in the process of low-temperature and short-time curing, a good pyramid structure is formed between the nano silver powder, the micron silver powder, the flaky silver powder, the resin and the substrate, so that the resistivity of the conductive main grid silver paste is reduced, the conductivity is increased, and the adhesion is also improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of HIT solar cells, and in particular to a conductive main grid silver paste for HIT solar cells and a preparation method thereof. Background Art

[0002] HIT (Heterojunction with Intrinsic Thin Layer) is a cell structure that adds a layer of non-doped (intrinsic) hydrogenated amorphous silicon thin film between p-type hydrogenated amorphous silicon and n-type hydrogenated amorphous silicon and the n-type silicon substrate. It is one of the solar cells that urgently needs to be mass-produced in China and occupies an extremely important position in the domestic market. Due to its different structure, the conductive silver paste on its surface is quite different from the silver paste on traditional crystalline silicon wafers. The silver paste on the surface of HIT is a low-temperature curing conductive silver paste. Low-temperature curing conductive silver paste must meet the following conditions: (1) low-temperature curing (curing below 220°C); (2) good electrical properties; (3) high adhesion; and (4) good environmental stability. However, the current domestic low-temperature curing conductive silver paste has the following shortcomings: the production time of HIT long-term low-temperature curing conductive main grid silver paste is long and the cost is relatively high; the existing HIT long-term low-temperature curing conductive main grid silver paste has low adhesion and high resistivity, and the time cost of HIT long-term low-temperature curing conductive main grid silver paste is high, resulting in low output. Therefore, in order to reduce costs and open up the domestic market, my country's research on low-temperature curing conductive silver paste for HIT still needs to be further improved. Summary of the Invention

[0003] The technical problem to be solved by the present invention is the long curing time, low adhesion and high resistance of the conductive main grid silver paste used in the existing HIT solar cells.

[0004] To solve the above technical problems, the present invention provides a conductive busbar silver paste for HIT solar cells, which comprises, by weight: 5 to 13 parts of an organic polymer resin, 30 to 60 parts of a first conductive powder, 30 to 60 parts of a second conductive powder, 0 to 5 parts of a curing agent, 1 to 10 parts of a solvent, and 0 to 5 parts of an auxiliary agent; the first conductive powder is flaky silver powder, and the second conductive powder is composed of nano silver powder and micron silver powder, and the micron silver powder is a highly dispersed, nearly spherical silver powder.

[0005] Compared to existing domestic low-temperature curing busbar silver pastes, the present invention achieves a near 100% cure rate at low temperatures in a short time by adding an organic polymer resin to the paste, utilizing a low activation energy resin and a catalytic curing agent. This shortens the curing time of the busbar silver paste for HIT solar cells. The micronized silver powder has good dispersibility and high activity, so during the low-temperature, short-time curing process, a good pyramid structure is formed between the nano-silver powder, micronized silver powder, flaky silver powder, resin, and substrate. This creates close contact between the silver powders, reduces contact resistance, reduces resistivity, and improves adhesion. Furthermore, the nano-silver powder and micronized silver powder act as auxiliary binders, shortening the paste's cure time, improving adhesion, and reducing the need for organic polymer resin, which also helps improve the paste's conductivity. The composite structure of nano-silver powder and micronized silver powder in the second conductive component ensures uniform microscopic mixing of the nano-silver powder and micronized silver powder. Furthermore, the micronized silver powder's high conductivity and sintering activity improve the screen printability, sintering activity, and electrical properties of the busbar silver paste. In addition to using organic polymer resin as a bonding phase, the conductive main grid silver paste provided by the present invention can also increase the adhesion of the bonding phase by sintering nanopowder during the curing process at 190-210° C. for 3-8 minutes, further improving the adhesion and reducing the resistivity.

[0006] Preferably, the second conductive powder comprises 10-30 parts nano-silver powder and 20-30 parts micron-silver powder. By further optimizing the raw material ratio of the second conductive powder, the nano-silver powder, micron-silver powder, and flaky silver powder can better interact with each other, facilitating close contact between the nano-silver powder, micron-silver powder, and flaky silver powder, thereby reducing resistivity and improving the conductivity of the conductive busbar silver paste.

[0007] Preferably, the method for preparing the micron silver powder comprises the following steps:

[0008] D1. Preparation of a silver nitrate dispersion: dissolving a dispersant in deionized water to form a dispersant solution; adding the dispersant solution to a 1-4 mol / L silver nitrate solution and stirring uniformly to form a silver nitrate dispersion, designated as solution A; the dispersant solution temperature is 25°C to 60°C, the molar ratio of silver nitrate to dispersant is 1:0.005-0.05, and the dispersant is cetyltrimethylammonium bromide;

[0009] D2. Preparation of silver slurry: Under the action of an ultrasonic water bath, a reducing agent solution is added dropwise to solution A, and the solution system temperature is maintained at 25°C to 60°C, so that silver nitrate and the reducing agent undergo a reduction reaction in the solution system to produce silver, which is recorded as mixed solution B; the reducing agent is a mixture of sodium ascorbate, glucose, and ascorbic acid; the molar ratio of silver nitrate to reducing agent is 1:0.5-3; the reduction reaction equation is as shown in formula (a):

[0010] 2Ag + +C6H8O6=2Ag↓+C6H6O6+2H + (a)

[0011] D3. Preparation and emulsification of wet silver powder: The mixed solution B was repeatedly washed with deionized water and filtered until the conductivity of the filtrate was less than 20 μs / cm, at which time the filtration was stopped to obtain wet silver powder; an emulsifier was added to the wet silver powder, and the mixture was emulsified and dispersed in a high-speed disperser at 3000 rpm for 20 minutes; the emulsifier was oleic acid or fatty acid, and the molar ratio of silver nitrate to emulsifier was 1:0.001-0.005;

[0012] D4. Preparation of micron silver powder: The emulsified and dispersed silver powder was dried in an oven at 65°C for 2 h, crushed with an air flow crusher, and sieved with a 200-mesh sieve to obtain highly dispersed, nearly spherical silver powder.

[0013] In steps D1 and D2 of the method for preparing micron silver powder, hexadecyltrimethylammonium bromide (CTAB) is selected as a dispersant, which has the following three main functions in the reaction: (1) forming a complex CTAB-Ag+ with Ag+ in the solution, changing the activity of Ag+, facilitating the smooth reaction, and achieving the purpose of preliminary dispersion; (2) CTAB can also complex with H+, increase the stability of H+, and promote the forward progress of formula (a); (3) the steric hindrance effect of the long chain of CTAB is large, wrapping the silver particles and hindering their continued growth, which can reduce the probability of collision between silver particles, reduce the generation of agglomeration, and make the silver powder particles more dispersed. The micron silver powder prepared by the above method has an average radius of 1 to 3 μm and a specific surface area of ​​0.1 to 2 m 2 / g, silver powder purity ≥99.5%, through the combination of micron silver powder, nano silver powder and flake silver powder, it can meet the comprehensive performance requirements of HIT solar cell conductive main grid silver paste in terms of screen printing suitability, sintering activity and electrical properties.

[0014] Preferably, the organic polymer resin includes one or more of acrylic resin, polyester resin, carbonate polyol, and silicone resin. Such organic polymer resins have better aging resistance and do not affect the electrical properties of the conductive busbar silver paste, thus facilitating the long-term stable operation of HIT solar cells.

[0015] Preferably, the average particle size of the nano silver powder is 20 to 100 nm, and the specific surface area is 1 to 10 m 2 / g, the average radius of the micron silver powder is 1 to 3 μm, and the specific surface area is 0.1 to 2 m 2 / g, tap density 1.5~3.5g / cm 3By optimizing the particle size and specific surface area of ​​nano-silver powder and micron-silver powder, the contact resistance between the silver powders in the conductive main grid silver paste and between the silver powders and the substrate can be further reduced.

[0016] Preferably, the average particle size of the flaky silver powder is 1 to 6 μm, the bulk density is 1 to 1.7 g / ml, and the tap density is 2 to 10 g / cm 3 Specific surface area 0.1~2m 2 / g. The particle size and tap density of the silver flake powder have a great influence on the conductive properties of the silver paste. If the particle size of the silver flake is too small, the electrical properties will be too poor; if the particle size of the silver flake is too large, the printability will be poor during the screen printing process. Therefore, the particle size of the silver flake powder is preferably 2-3μm and the tap density is 2-10g / cm 3 .

[0017] Preferably, the particle size of the flaky silver powder is preferably 2 to 3 μm. Further optimization of the particle size of the flaky silver can make the conductive busbar silver paste have high conductivity while being easy to process.

[0018] Preferably, the curing agent comprises at least one of blocked isocyanate, boron trifluoride, polyamine, and acid anhydride. Such curing agents do not react with the resin at room temperature, but upon heating, expose active functional groups to undergo cross-linking reaction with the active portions of the resin to cure.

[0019] Preferably, the solvent includes at least one of butyl carbitol, butyl carbitol acetate, terpineol, terpineol, dioctyl phthalate, and dimethyl phthalate. During the preparation of the organic vehicle, the solvent dissolves the binder phase. When the conductive silver powder is added to the organic vehicle, the solvent allows it to be better dispersed in the resin, further improving adhesion.

[0020] The present invention also provides a method for preparing the conductive busbar silver paste for HIT solar cells, comprising the following steps:

[0021] S1. Prepare the raw materials required for pulping: select organic polymer resin, first conductive powder, second conductive powder, curing agent, solvent, and additives;

[0022] S2. Preparation of organic vehicle: Weigh 5-13 parts of organic polymer resin, 0-5 parts of curing agent, 1-10 parts of solvent, and 0-5 parts of additive, pour into a double planetary mixer, control the temperature at 25°C, set the dispersion disk speed at 70 r / min, and stir at 40 r / min for 20 minutes to form an organic vehicle;

[0023] S3, preparing a coarse silver paste: weighing 30-60 parts of the first conductive powder and 30-60 parts of the second conductive powder, and pouring 6-10 parts of the organic vehicle prepared in step S2 into a double planetary mixer, controlling the temperature at 25°C, the dispersion disk speed at 80 r / min, and the stirring speed at 50 r / min, stirring for 3-6 hours until the coarse silver paste is formed;

[0024] S4. Preparation of fine silver paste: The coarse silver paste is subjected to multi-step rolling using a three-roll mill at a rolling temperature of 20° C., and finally a finished fine silver paste with a thickness of less than 10 μm is obtained.

[0025] By using the above method, a conductive busbar silver paste can be prepared with a curing condition of 195°C for 6.5 minutes and a maximum adhesion of 2.3 N / mm; a curing condition of 210°C for 3.5 minutes and a maximum adhesion of 2.6 N / mm.

[0026] The beneficial effects of the conductive main grid silver paste of the present invention for HIT solar cells with short-time low-temperature curing and high adhesion are:

[0027] a) Solve the problem that the existing HIT main grid paste has a long curing time and needs to be cured at 200-220°C for 20-30 minutes, resulting in high time cost for HIT production. The curing condition of the silver paste of the present invention is to dry it at 160-170°C for 3-5 minutes, so that the solvent can be completely volatilized before curing, so that the adhesive phase and the conductive phase can be cured in a shorter time, saving time cost. The present invention adopts a resin with low activation energy and a catalytic curing agent, so that the organic carrier and silver powder can reach a curing degree close to 100% in a short time, which not only saves the time cost of curing, but also reduces the resistivity of the HIT solar cell and improves its adhesion.

[0028] b) Solve the problem of high resistivity and low adhesion of HIT main grid paste during short-term curing. The micron silver powder prepared in the present invention has good dispersibility and high activity, so in the process of low-temperature and short-term curing, the nano silver powder, micron silver powder, flaky silver powder, organic carrier and substrate are combined into a pyramid structure with good contact. The silver powders are in very close contact, and the contact resistance is small, which reduces the resistivity and improves the adhesion. In the present invention, in the process of low-temperature and short-term curing, a good pyramid structure is formed between the nano silver powder, micron silver powder, flaky silver powder, resin and substrate, which reduces the resistivity and improves the adhesion. Secondly, the present invention first prepares the organic carrier and then prepares the silver paste. In the process of preparing the organic carrier, the solvent plays a role in dissolving the binding phase, and then the conductive silver powder is added to the organic carrier to better disperse the conductive silver powder into the resin, further improving the adhesion. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1This is the SEM morphology of the micron silver powder prepared in Example 1;

[0030] Figure 2 The conductive busbar silver paste prepared in Example 1 is applied to a substrate, and a cross-sectional SEM image of the substrate and the silver paste after curing;

[0031] Figure 3 This is an SEM morphology of the conductive busbar silver paste prepared in Example 1 after curing. DETAILED DESCRIPTION

[0032] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is described in detail below with reference to specific embodiments.

[0033] Example 1

[0034] A conductive busbar silver paste for HIT solar cells, comprising, by weight: 5.5 parts polyester resin, 2 parts acrylic resin, 0.5 parts polyvinyl acetate, 45 parts flaky silver powder, 25 parts micron silver powder, 20 parts nano silver powder, 0.15 parts boron trifluoride, 2 parts butyl carbitol acetate, and 0.2 parts additives. The flaky silver powder has an average particle size of 1 to 6 μm, a bulk density of 1 to 1.7 g / ml, and a tap density of 2 to 10 g / cm 3 Specific surface area 0.1~12m 2 / g, the average particle size of nano silver powder is 20-100nm, the specific surface area is 1-10m 2 / g, the average particle size of micron silver powder is 1-3 μm, and the specific surface area is 0.1-2 m 2 / g, tap density 1.5~3.5g / cm 3 .

[0035] The micron silver powder in this embodiment is prepared by the following steps:

[0036] D1. Preparation of a silver nitrate dispersion: Dissolve a dispersant in deionized water to form a dispersant solution; add the dispersant solution to a 2 mol / L silver nitrate solution and stir to form a silver nitrate dispersion, referred to as solution A; the dispersant solution is heated to 40°C, the molar ratio of silver nitrate to dispersant is 1:0.03, and the dispersant is hexadecyltrimethylammonium bromide;

[0037] D2. Preparation of silver slurry: Under the action of an ultrasonic water bath, a reducing agent solution was added dropwise to solution A, and the solution system temperature was maintained at 40°C. Silver nitrate and the reducing agent underwent a reduction reaction in the solution system to produce silver, which was recorded as mixed solution B. The reducing agent was a mixture of sodium ascorbate, glucose, and ascorbic acid. The molar ratio of silver nitrate to reducing agent was 1:2. The reduction reaction equation was as shown in formula (a):

[0038] 2Ag + +C6H8O6=2Ag↓+C6H6O6+2H + (a)

[0039] D3. Preparation and emulsification of wet silver powder: The mixed solution B was repeatedly washed with deionized water and filtered until the conductivity of the filtrate was <20 μs / cm, at which time the filtration was stopped to obtain wet silver powder. An emulsifier was added to the wet silver powder and emulsified and dispersed in a high-speed disperser at 3000 rpm for 20 minutes. The emulsifier was oleic acid and fatty acid, and the molar ratio of silver nitrate to emulsifier was 1:0.003.

[0040] D4. Preparation of micron silver powder: The emulsified and dispersed silver powder was dried in an oven at 65°C for 2 h, crushed with an air flow crusher, and sieved with a 200-mesh sieve to obtain highly dispersed, nearly spherical silver powder.

[0041] The surface morphology SEM image of the micron silver powder prepared by the above method is as follows: Figure 1 As shown by Figure 1 It can be seen that the micron silver powder particles are nearly spherical and have a particle size of 1 to 3 μm.

[0042] In this embodiment, the preparation of a conductive busbar silver paste for a HIT solar cell includes the following steps:

[0043] S1. Prepare the raw materials required for pulping: select polyester resin, acrylic resin, polyvinyl acetate, flaky silver powder, nano silver powder, boron trifluoride, butyl carbitol acetate and additives.

[0044] S2. Preparation of an organic vehicle: Weigh 5.5 parts of polyester resin, 2 parts of acrylic resin, 0.5 parts of polyvinyl acetate, 0.15 parts of boron trifluoride, 2 parts of butyl carbitol acetate, and 0.2 parts of an additive, and pour them into a double planetary mixer. Control the temperature at 25°C, set the dispersing disk speed at 70 rpm, and stir at 40 rpm for 20 minutes to form an organic vehicle.

[0045] S3. Prepare a coarse silver paste: Weigh 45 parts of flaky silver powder, 25 parts of micron silver powder, and 20 parts of nano silver powder, pour the organic vehicle prepared in step S2 into a double planetary mixer, control the temperature at 25°C, set the dispersion disk speed at 80 r / min, and the stirring speed at 50 r / min, and stir for 4 hours to form a coarse silver paste;

[0046] S4. Preparation of fine silver paste: The coarse silver paste is subjected to multi-step rolling using a three-roll mill. The rolling temperature is 20°C, and the gaps between the three processes are 120μm, 80μm; 80μm, 50μm; 50μm, 25μm respectively. Each rolling process is repeated 7 times, and finally a finished fine silver paste with a thickness of less than 10μm is obtained.

[0047] The conductive main grid silver paste prepared in this embodiment is applied on the substrate, and the nano silver powder, micron silver powder, flaky silver powder, organic carrier and substrate are combined to form a pyramid structure with good contact, such as Figure 2 The silver powders shown are in very close contact with each other, resulting in low contact resistance, which reduces resistivity and improves adhesion.

[0048] Although in this embodiment, the organic polymer resin only uses polyester resin, acrylic resin, and polyvinyl acetate, in other embodiments, the organic polymer resin may also be selected from one or more of acrylic resin, polyester resin, carbonate polyol, silicone resin, polyurethane prepolymer, polyvinyl acetate, polyamide, and polyamine. Since these organic polymer resins have similar properties to the organic polymer resin used in this embodiment, the same technical effects as those of this embodiment can be achieved in other embodiments.

[0049] Although boron trifluoride is selected as the curing agent in this embodiment, in other embodiments, the curing agent can be selected from at least one of blocked isocyanate, boron trifluoride, polyamine, and acid anhydride, and the same technical effect as boron trifluoride in this embodiment can be achieved.

[0050] Although butyl carbitol acetate is selected as the solvent in this embodiment, in other embodiments, the curing agent can be selected from at least one of butyl carbitol, butyl carbitol acetate, terpineol, terpineol, dioctyl phthalate, and dimethyl phthalate, and the same technical effect as tributyl carbitol acetate in this embodiment can be achieved.

[0051] Example 2

[0052] A conductive busbar silver paste for HIT solar cells, comprising, by weight: 2.5 parts polyester resin, 2.2 parts acrylic resin, 0.3 parts polyvinyl acetate, 60 parts flaky silver powder, 20 parts micron silver powder, 30 parts nano silver powder, 5 parts boron trifluoride, 1 part butyl carbitol acetate, and 2 parts additives. The average particle size of the flaky silver powder is 1-6 μm, the bulk density is 1-1.7 g / ml, and the tap density is 2-10 g / cm 3 Specific surface area 0.1~2m 2 / g, the average particle size of nano silver powder is 20-100nm, the specific surface area is 1-10m 2 / g, the average particle size of micron silver powder is 1-3 μm, and the specific surface area is 0.1-2 m 2 / g, tap density 1.5~3.5g / cm 3 .

[0053] The micron silver powder in this embodiment is prepared by the following steps:

[0054] D1. Preparation of a silver nitrate dispersion: Dissolve a dispersant in deionized water to form a dispersant solution; add the dispersant solution to a 1 mol / L silver nitrate solution and stir to form a silver nitrate dispersion, designated as solution A; the dispersant solution is heated to 60° C., and the molar ratio of silver nitrate to dispersant is 1:0.005. The dispersant is hexadecyltrimethylammonium bromide.

[0055] D2. Preparation of silver slurry: Under the action of an ultrasonic water bath, a reducing agent solution was added dropwise to solution A, and the solution system temperature was maintained at 60° C., so that silver nitrate and the reducing agent underwent a reduction reaction in the solution system to produce silver, which was recorded as mixed solution B. The reducing agent was a mixture of sodium ascorbate, glucose, and ascorbic acid; the molar ratio of silver nitrate to reducing agent was 1:0.5; the reduction reaction equation was as shown in formula (a):

[0056] 2Ag + +C6H8O6=2Ag↓+C6H6O6+2H + (a)

[0057] D3. Preparation and emulsification of wet silver powder: The mixed solution B was repeatedly washed with deionized water and filtered until the conductivity of the filtrate was <20 μs / cm, at which time the filtration was stopped to obtain wet silver powder. An emulsifier was added to the wet silver powder, and the mixture was emulsified and dispersed in a high-speed disperser at 3000 rpm for 20 minutes. The emulsifier was oleic acid or fatty acid, and the molar ratio of silver nitrate to emulsifier was 1:0.005.

[0058] D4. Preparation of micron silver powder: The emulsified and dispersed silver powder was dried in an oven at 65°C for 2 h, crushed with an air flow crusher, and sieved with a 200-mesh sieve to obtain highly dispersed, nearly spherical silver powder.

[0059] In this embodiment, the preparation of a conductive busbar silver paste for a HIT solar cell includes the following steps:

[0060] S1. Prepare the raw materials required for pulping: select polyester resin, acrylic resin, polyvinyl acetate, flake silver powder, nano silver powder, boron trifluoride, butyl carbitol acetate and additives;

[0061] S2. Preparation of an organic vehicle: Weigh 2.5 parts of polyester resin, 2.2 parts of acrylic resin, 0.3 parts of polyvinyl acetate, 5 parts of boron trifluoride, 1 part of butyl carbitol acetate, and 2 parts of an additive, pour them into a double planetary mixer, control the temperature at 25°C, set the dispersion disk speed at 70 r / min, and the stirring speed at 40 r / min, and stir for 20 minutes to form an organic vehicle;

[0062] S3. Prepare a coarse silver paste: Weigh 60 parts of flaky silver powder, 20 parts of micron silver powder, and 30 parts of nano silver powder, pour the organic vehicle prepared in step S2 into a double planetary mixer, control the temperature at 25°C, set the dispersion disk speed at 80 r / min, and the stirring speed at 50 r / min, and stir for 3 hours until the coarse silver paste is formed;

[0063] S4. Preparation of fine silver paste: The coarse silver paste is subjected to multi-step rolling on a three-roll mill. The rolling temperature is 20°C, and the gaps between the three processes are 120μm, 80μm; 80μm, 50μm; 50μm, 25μm respectively. Each rolling process is performed 6 times, and finally a finished fine silver paste with a thickness of less than 10μm is obtained.

[0064] Example 3

[0065] A conductive busbar silver paste for HIT solar cells, comprising, by weight, 5.5 parts polyester resin, 4.5 parts acrylic resin, 30 parts flaky silver powder, 30 parts micron silver powder, 10 parts nano silver powder, 10 parts butyl carbitol acetate, and 1 part additive. The flaky silver powder has an average particle size of 1 to 6 μm, a bulk density of 1 to 1.7 g / ml, and a tap density of 2 to 10 g / cm 3 Specific surface area 0.1~2m 2 / g, the average particle size of nano silver powder is 20-100nm, the specific surface area is 1-10m 2 / g, the average particle size of the micron silver powder is 1 to 3 μm, and the specific surface area is 0.1 to 2 m 2 / g, tap density 1.5~3.5g / cm 3 .

[0066] The micron silver powder in this embodiment is prepared by the following steps:

[0067] D1. Preparation of a silver nitrate dispersion: Dissolve a dispersant in deionized water to form a dispersant solution; add the dispersant solution to a 4 mol / L silver nitrate solution and stir to form a silver nitrate dispersion, designated as solution A; the dispersant solution is heated to 25° C., the molar ratio of silver nitrate to dispersant is 1:0.05, and the dispersant is hexadecyltrimethylammonium bromide;

[0068] D2. Preparation of silver slurry: Under the action of an ultrasonic water bath, a reducing agent solution was added dropwise to solution A, and the solution system temperature was maintained at 25° C., so that silver nitrate and the reducing agent underwent a reduction reaction in the solution system to produce silver, which was recorded as mixed solution B. The reducing agent was a mixture of sodium ascorbate, glucose, and ascorbic acid; the molar ratio of silver nitrate to reducing agent was 1:3; the reduction reaction equation was as shown in formula (a):

[0069] 2Ag + +C6H8O6=2Ag↓+C6H6O6+2H+ (a)

[0070] D3. Preparation and emulsification of wet silver powder: The mixed solution B was repeatedly washed with deionized water and filtered until the conductivity of the filtrate was <20 μs / cm, at which time the filtration was stopped to obtain wet silver powder. An emulsifier was added to the wet silver powder and emulsified and dispersed in a high-speed disperser at 3000 rpm for 20 minutes. The emulsifier was oleic acid or fatty acid, and the molar ratio of silver nitrate to emulsifier was 1:0.001.

[0071] D4. Preparation of micron silver powder: The emulsified and dispersed silver powder was dried in an oven at 65°C for 2 h, crushed with an air flow crusher, and sieved with a 200-mesh sieve to obtain highly dispersed, nearly spherical silver powder.

[0072] In this embodiment, the preparation of a conductive busbar silver paste for a HIT solar cell includes the following steps:

[0073] S1. Prepare the raw materials required for pulping: select polyester resin, acrylic resin, flake silver powder, nano silver powder, boron trifluoride, butyl carbitol acetate and additives;

[0074] S2. Preparation of an organic vehicle: Weigh 5.5 parts of polyester resin, 4.5 parts of acrylic resin, 10 parts of butyl carbitol acetate, and 1 part of an additive, and pour them into a double planetary mixer. Control the temperature at 25°C, set the dispersing disk speed at 70 rpm, and stir at 40 rpm for 20 minutes to form an organic vehicle.

[0075] S3. Prepare a coarse silver paste: Weigh 30 parts of flaky silver powder, 30 parts of micron silver powder, and 10 parts of nano silver powder, pour the organic vehicle prepared in step S2 into a double planetary mixer, control the temperature at 25°C, set the dispersion disk speed at 80 r / min, and the stirring speed at 50 r / min, and stir for 6 hours to form a coarse silver paste;

[0076] S4. Preparation of fine silver paste: The coarse silver paste is subjected to multi-step rolling using a three-roll mill. The rolling temperature is 20°C, and the gaps between the three processes are 120μm, 80μm; 80μm, 50μm; 50μm, 25μm respectively. Each rolling process is performed 8 times, and finally a finished fine silver paste with a thickness of less than 10μm is obtained.

[0077] Example 4

[0078] A conductive busbar silver paste for HIT solar cells, comprising, by weight, 5.5 parts polyester resin, 2.45 parts polyvinyl acetate, 45 parts flaky silver powder, 25 parts nano silver powder, 20 parts micron silver powder, 0.15 parts boron trifluoride, and 2 parts butyl carbitol acetate. The flaky silver powder has an average particle size of 1 to 6 μm, a bulk density of 1 to 1.7 g / ml, and a tap density of 2 to 10 g / cm3 Specific surface area 0.1~2m 2 / g, the average particle size of nano silver powder is 20-100nm, the specific surface area is 1-10m 2 / g, the average particle size of the micron silver powder is 1 to 3 μm, and the specific surface area is 0.1 to 2 m 2 / g, tap density 1.5~3.5g / cm 3 .

[0079] The micron silver powder in this embodiment is prepared by the following steps:

[0080] D1. Preparation of a silver nitrate dispersion: Dispersant was dissolved in deionized water to form a dispersant solution; the dispersant solution was added to a 3 mol / L silver nitrate solution and stirred to form a silver nitrate dispersion, designated as solution A; the dispersant solution was heated to 35°C, the molar ratio of silver nitrate to dispersant was 1:0.02, and the dispersant was cetyltrimethylammonium bromide;

[0081] D2. Preparation of silver slurry: Under the action of an ultrasonic water bath, a reducing agent solution was added dropwise to solution A, and the solution system temperature was maintained at 35°C, so that silver nitrate and the reducing agent underwent a reduction reaction in the solution system to produce silver, which was recorded as mixed solution B. The reducing agent was a mixture of sodium ascorbate, glucose, and ascorbic acid; the molar ratio of silver nitrate to reducing agent was 1:1; the reduction reaction equation was as shown in formula (a):

[0082] 2Ag + +C6H8O6=2Ag↓+C6H6O6+2H + (a)

[0083] D3. Preparation and emulsification of wet silver powder: The mixed solution B was repeatedly washed with deionized water and filtered until the conductivity of the filtrate was <20 μs / cm, at which time the filtration was stopped to obtain wet silver powder; an emulsifier was added to the wet silver powder, and the mixture was emulsified and dispersed in a high-speed disperser at 3000 rpm for 20 minutes; the emulsifier was oleic acid and fatty acid, and the molar ratio of silver nitrate to emulsifier was 1:0.002;

[0084] D4. Preparation of micron silver powder: The emulsified and dispersed silver powder was dried in an oven at 65°C for 2 h, crushed with an air flow crusher, and sieved with a 200-mesh sieve to obtain highly dispersed, nearly spherical silver powder.

[0085] In this embodiment, the preparation of a conductive busbar silver paste for a HIT solar cell includes the following steps:

[0086] S1. Prepare the raw materials required for pulping: polyester resin, polyvinyl acetate, flake silver powder, nano silver powder, micron silver powder, boron trifluoride, and butyl carbitol acetate;

[0087] S2. Preparation of an organic vehicle: Weigh 5.5 parts of polyester resin, 2.45 parts of polyvinyl acetate, 0.15 parts of boron trifluoride, and 2 parts of butyl carbitol acetate, pour into a double planetary mixer, control the temperature at 25°C, set the dispersion disk speed at 70 rpm, and stir at 40 rpm for 20 minutes to form an organic vehicle;

[0088] S3. Prepare a coarse silver paste: Weigh 45 parts of flaky silver powder, 25 parts of nano silver powder, and 20 parts of micron silver powder, pour the organic vehicle prepared in step S2 into a double planetary mixer, control the temperature at 25°C, set the dispersion disk speed at 80 r / min, and the stirring speed at 50 r / min, and stir for 5 hours to form a coarse silver paste;

[0089] S4. Preparation of fine silver paste: The coarse silver paste is subjected to multi-step rolling on a three-roll mill. The rolling temperature is 20°C, and the gaps between the three processes are 120μm, 80μm; 80μm, 50μm; 50μm, 25μm respectively. Each rolling process is performed 6 times, and finally a finished fine silver paste with a thickness of less than 10μm is obtained.

[0090] Example 5

[0091] A conductive busbar silver paste for HIT solar cells, comprising, by weight, 5.5 parts polyester resin, 2.45 parts silicone resin, 45 parts flaky silver powder, 25 parts nano silver powder, 20 parts micron silver powder, 0.15 parts boron trifluoride, 2 parts butyl carbitol acetate, and 0.2 parts additive. The flaky silver powder has an average particle size of 1 to 6 μm, a bulk density of 1 to 1.7 g / ml, and a tap density of 2 to 10 g / cm 3 Specific surface area 0.1~2m 2 / g, the average particle size of nano silver powder is 20-100nm, the specific surface area is 1-10m 2 / g, the average particle size of the micron silver powder is 1 to 3 μm, and the specific surface area is 0.1 to 2 m 2 / g, tap density 1.5~3.5g / cm 3 .

[0092] The micron silver powder in this embodiment is prepared by the following steps:

[0093] D1. Preparation of a silver nitrate dispersion: Dissolve polyvinylpyrrolidone (PVP) in deionized water to form a dispersant solution; add the dispersant solution to a 3 mol / L silver nitrate solution and stir to form a silver nitrate dispersion, referred to as solution A; the dispersant solution temperature is 25° C., and the molar ratio of silver nitrate to dispersant is 1:0.005;

[0094] D2. Preparation of silver slurry: Under the action of an ultrasonic water bath, a reducing agent solution was added dropwise to solution A, maintaining the solution system temperature at 25°C, to allow silver nitrate and the reducing agent to undergo a reduction reaction within the system to produce silver, which is recorded as solution B. The reducing agent was a mixture of sodium ascorbate, glucose, and ascorbic acid; the molar ratio of silver nitrate to reducing agent was 1:0.5.

[0095] D3. Preparation and emulsification of wet silver powder: Solution B was repeatedly washed with deionized water and filtered until a filtrate with a conductivity of <20 μs / cm was obtained, thereby obtaining wet silver powder. An emulsifier was added to the wet silver powder, and the mixture was emulsified and dispersed in a high-speed disperser at 3000 rpm for 20 minutes. The emulsifier was oleic acid or fatty acid, and the molar ratio of silver nitrate to emulsifier was 1:0.001.

[0096] D4. Preparation of micron silver powder: The emulsified and dispersed silver powder was dried in an oven at 65°C for 2 h, crushed with an air flow crusher to smooth the irregular shapes on the silver powder surface, and sieved with a 200-mesh sieve to obtain highly dispersed, nearly spherical silver powder.

[0097] In this embodiment, the preparation of a conductive busbar silver paste for a HIT solar cell includes the following steps:

[0098] S1. Prepare the raw materials required for pulping: select polyester resin, silicone resin, flake silver powder 45, nano silver powder, micron silver powder, boron trifluoride, butyl carbitol acetate and additives;

[0099] S2. Preparation of an organic vehicle: Weigh 5.5 parts of polyester resin, 2.45 parts of silicone resin, 0.15 parts of boron trifluoride, 2 parts of butyl carbitol acetate, and 0.2 parts of an additive, and pour them into a double planetary mixer. Control the temperature at 25°C, set the dispersing disk speed at 70 rpm, and stir at 40 rpm for 20 minutes to form an organic vehicle.

[0100] S3. Prepare a coarse silver paste: Weigh 45 parts of flaky silver powder, 25 parts of nano silver powder, and 20 parts of micron silver powder, pour the organic vehicle prepared in step S2 into a double planetary mixer, control the temperature at 25°C, set the dispersion disk speed at 80 r / min, and the stirring speed at 50 r / min, and stir for 3 hours to form a coarse silver paste;

[0101] S4. Preparation of fine silver paste: The coarse silver paste is subjected to multi-step rolling using a three-roll mill. The rolling temperature is 20°C, and the gaps between the three processes are 120μm, 80μm; 80μm, 50μm; 50μm, 25μm respectively. Each rolling process is performed 8 times, and finally a finished fine silver paste with a thickness of less than 10μm is obtained.

[0102] The weight formulas of the components in Examples 1-5 are shown in Table 1.

[0103] Table 1 Weight formula of each component in Examples 1 to 5

[0104]

[0105] The short-time curing conditions adopted in the present invention are curing at 195° C. for 6.5 minutes and curing at 210° C. for 3.5 minutes.

[0106] The testing method for the conductive busbar silver pastes prepared in Examples 1 to 5 above is as follows:

[0107] Viscosity: The viscosity of the slurry was tested using a Mars40 dynamic shear rheometer in DV2T mode with a temperature control of 25°C.

[0108] Resistivity after curing: Print a fixed pattern on the test piece, measure the resistance value after curing (0.6 × 60 mm), and calculate the resistivity according to the formula R = ρ·L / S;

[0109] Film thickness: After curing, the film thickness is measured using a handheld resistance meter (the line resistance and film thickness are both averaged);

[0110] Adhesion: Pull strength of weld test after curing.

[0111] The test results are shown in Tables 2 and 3.

[0112] Table 2: Test performance data results of curing at 195℃ for 6.5 minutes.

[0113]

[0114] Table 3: Test performance data results of curing at 210℃ for 3.5 minutes.

[0115]

[0116]

[0117] The formula of the conductive main grid silver paste with short-time low-temperature curing and high adhesion for HIT solar cells of the present invention has a great influence on the electrical properties and adhesion of the silver paste. Within the formula range of the present invention, the above-mentioned Example 1, calculated by weight, comprises 8 parts of organic polymer resin, 45 parts of first conductive powder, 45 parts of second conductive powder, 0.15 parts of curing agent, 2 parts of solvent, and 0.2 parts of auxiliary agent. After curing, the paste has low resistivity, good viscosity, is easy to print, has high adhesion after curing, and has low production cost. The curing conditions are 195°C, and at 6.5 minutes, the maximum peak adhesion reaches 2.3N / mm, and the adhesion range is above 2N / mm; the curing conditions are 210°C, and at 3.5 minutes, the maximum peak adhesion reaches 2.6N / mm, and the adhesion range is above 1.5N / mm. The conductive main grid silver paste prepared in Example 1 is applied to a substrate. The cross-sectional SEM morphology of the substrate and the silver paste at a magnification of 3000 times after curing is as shown in the figure. Figure 2 As shown by Figure 2 It can be seen that on the surface of the substrate, the silver paste is in close contact with the substrate, and the nano silver powder, micro silver powder, flaky silver powder, resin and substrate are combined to form a pyramid structure with good contact. The SEM morphology of the conductive main grid silver paste prepared in Example 1 after curing at a magnification of 10,000 times is shown as follows: Figure 3 As shown by Figure 3 It can be seen that the nano silver powder, micron silver powder and flaky silver powder in the solidified silver paste are in very close contact.

[0118] Although the present disclosure is disclosed as above, the protection scope of the present disclosure is not limited thereto. Those skilled in the art can make various changes and modifications without departing from the spirit and scope of the present disclosure, and these changes and modifications will fall within the protection scope of the present invention.

Claims

1. A conductive main grid silver paste for HIT solar cells, characterized in that: The invention comprises, by weight, 5-13 parts of an organic polymer resin, 30-60 parts of a first conductive powder, 30-60 parts of a second conductive powder, 0-5 parts of a curing agent, 1-10 parts of a solvent, and 0-5 parts of an auxiliary agent; the first conductive powder is flaky silver powder, the second conductive powder is composed of nano silver powder and micron silver powder, and the micron silver powder is a highly dispersible nearly spherical silver powder; the organic polymer resin is a combination of polyester resin, acrylic resin and polyvinyl acetate, or a combination of polyester resin and acrylic resin, or a combination of polyester resin and polyacrylic resin, or a combination of polyester resin and silicone resin; the curing agent comprises at least one of blocked isocyanate, boron trifluoride, polyamine, and acid anhydride; the second conductive powder comprises 10-30 parts of nano silver powder and 20-30 parts of micron silver powder; the particle size of the flaky silver powder is 2-3 μm, and the tap density is 2-10 g / cm 3 .

2. The conductive main grid silver paste for HIT solar cells according to claim 1, characterized in that: The micron silver powder is prepared by the following steps: D1. Preparation of silver nitrate dispersion: dissolving a dispersant in deionized water to form a dispersant solution; adding the dispersant solution to a silver nitrate solution having a concentration of 1-4 mol / L, and stirring to form a silver nitrate dispersion, which is referred to as solution A; the temperature of the dispersant solution is 25°C-60°C, the molar ratio of silver nitrate to the dispersant is 1:0.005-0.05, and the dispersant is hexadecyltrimethylammonium bromide; D2. Preparation of silver slurry: under the action of an ultrasonic water bath, a reducing agent solution is added dropwise to solution A, and the temperature of the solution system is maintained at 25°C to 60°C, so that silver nitrate and the reducing agent undergo a reduction reaction in the solution system to generate silver, which is recorded as mixed solution B; the reducing agent is a mixture of sodium ascorbate, glucose and ascorbic acid; the molar ratio of silver nitrate to the reducing agent is 1:0.5-3; the reduction reaction equation is as shown in formula (a): <h2 style=";text-align:left;direction:ltr">2Ag<h2 style=";text-align:left;direction:ltr"> + <h2 style=";text-align:left;direction:ltr"> +C6H8O6 = 2Ag↓+C6H6O6+2H<h2 style=";text-align:left;direction:ltr"> + <h2 style=";text-align:left;direction:ltr"> (a) D3, preparation and emulsification of wet silver powder: the mixed solution B is repeatedly washed with deionized water and filtered until the conductivity of the filtrate is less than 20 μs / cm, and the filtration is stopped to obtain wet silver powder; an emulsifier is added to the wet silver powder, and emulsified and dispersed in a high-speed disperser at 3000 r / min for 20 minutes; the emulsifier is oleic acid and fatty acid, and the molar ratio of silver nitrate to emulsifier is 1:0.001-0.005; D4. Preparation of micron silver powder: The emulsified and dispersed silver powder was dried in an oven at 65° C. for 2 h, crushed with an air flow crusher, and sieved with a 200-mesh sieve to obtain micron silver powder.

3. The conductive main grid silver paste for HIT solar cells according to claim 1, characterized in that: The average particle size of the nano silver powder is 20-100 nm, and the specific surface area is 1-10 m 2 / g, the average particle size of the micron silver powder is 1-3 μm, and the specific surface area is 0.1-2 m 2 / g, tap density 1.5~3.5g / cm 3 .

4. The conductive main grid silver paste for HIT solar cells according to claim 1, characterized in that: The particle size of the flaky silver powder is 2-3 μm.

5. The conductive main grid silver paste for HIT solar cells according to claim 1, characterized in that: The solvent includes at least one of butyl carbitol, butyl carbitol acetate, terpineol, terpineol, dioctyl phthalate, and dimethyl phthalate.

6. A method for preparing a conductive main grid silver paste for a HIT solar cell according to claim 1, characterized in that: The following steps are involved: S1. Prepare the raw materials required for pulping: select organic polymer resin, first conductive powder, second conductive powder, curing agent, solvent, and additive; S2. Preparation of organic carrier: weigh 5-13 parts of organic polymer resin, 0-5 parts of curing agent, 1-10 parts of solvent, and 0-5 parts of auxiliary agent, pour into a double planetary mixer, control the temperature at 25°C, set the dispersion disk speed at 70r / min, and the stirring speed at 40r / min, and stir for 20min to form an organic carrier; S3, preparing a crude silver paste: weighing 30-60 parts of the first conductive powder and 30-60 parts of the second conductive powder, pouring 6-10 parts of the organic carrier prepared in step S2 into a double planetary mixer, controlling the temperature at 25°C, the dispersion disk speed at 80r / min, the stirring speed at 50r / min, stirring for 3-6h, and stirring evenly to form a crude silver paste; S4. Preparation of fine silver paste: The coarse silver paste is subjected to multi-step rolling by a three-roll mill at a rolling temperature of 20° C., and finally a finished fine silver paste with a particle size of less than 10 μm is obtained.

Citation Information

Patent Citations

  • Conductive paste for HJT battery and preparation method of conductive paste

    CN112071468A

  • Method for preparing silver powder through space confinement method

    CN112276108A

  • HJT battery low-temperature curing silver paste for fine printing and preparation method thereof

    CN113345623A